Categorização da doença de Parkinson de acordo com a presença de transtorno comportamental do sono rem: associação com disfunção autonômica e gravidade da doença - Pérola de Oliveira (2021)
Introduction Parkinson's disease (PD) has several clinical manifestations and distinct prognoses. It is characterized by a set of motor and non-motor symptoms that can range from independence to complete incapacity for work and personal care. So far, it is not clear which would be the subtype markers of the disease that could alert to forms of worse prognosis. However, there are some studies showing that the presence of REM sleep behavior disorder (RBD) may be associated with faster progression of motor symptoms and is related to the presence of other non-motor symptoms such as autonomic dysfunction and cognitive decline. It is also questioned whether dysautonomia are primarily associated with RBD, as they are reported in idiopathic forms of this sleep disorder and share some central regulatory nuclei, or if they are more severe in patients diagnosed with PD and RBD, thus marking a subtype of disease. Objectives The aim of this study is to determine whether RBD is a PD subtype marker and whether autonomic dysfunctions in PD patients are primarily RBD associated. Methods A total of 120 patients diagnosed with PD and 48 controls were evaluated. PD patients were classified into two subgroups according to the presence or absence of RBD. Scales were applied to assess the stage of the disease and degree of disability using the Hoehn Yahr (HY) scales and the Schwab and England daily life activities scale and the complete Movement Disorders Society Unified Parkinson’s Disease Rating Scale (MDS-UPDRS). Folstein's mini-mental state examination was applied to screen for cognitive decline and the Parkinson Disease Questionnaire – 39 (PDQ-39) was used to assess quality of life. All participants underwent brain magnetic resonance, polysomnography and autonomic reactivity tests. Results A total of 120 patients with PD were evaluated, 55 with PD+RBD and 65 without RBD. Among the medications used, there was a higher percentage of levodopa use in patients with RBD (p = 0.04). In the analysis of the neurological examination, the presence of normal gait was observed most commonly in the subgroup that does have TCSR (p = 0.01) and greater use of locomotion aid in the subgroup with TCSR (p = 0.005). In the evaluation of the applied scales, the scale of activities of daily living by Schwab and England showed the smallest score in the TCSR group (p = 0.001). In relation to part II of the MDS-UPDRS, related to the motor aspects of daily life experiences, it presented a higher score in patients with TCSR (p = 0.02). Dysautonomia was more frequent in patients with RBD (p = 0.002). Conclusion In conclusion, this study suggests that PD and RBD patients have more severe PD phenotype with greater dependence, more motor symptoms and more marked dysautonomic changes.